(untitled) (Biological Sciences - PJSIR, 2023)
Fossil remains of Gazella sp., Dorcatherium majus and Gaindatherium browni are recovered from the middle Miocene (14.2-11.2 Ma) of Bhilomar, Chakwal, Punjab, Pakistan. The sample comprises upper and lower dentitions. Presence of above fossil families in the Chinji formation depicts more faunal elements in this zone and their abundance. The Siwalik group has yielded an abundant vertebrate fauna which consists of almost all type of mammalian groups.